Surface Charge Effects on Adsorption of Solutes by Poplar and Elm Biochars - Steven C. Peterson; Sanghoon Kim; Jason Adkins (C, 2021)
Elm and poplar are two tree species that can provide a large amount of low-value feedstock for biochar production due to their rapid growth rate (poplar), and susceptibility to disease and/or infestation (both elm and poplar). Biochar has been studied recently as filtration medium for water purification, as it provides a renewable alternative to activated carbon. In this work, the adsorption efficiency of biochars made from elm and poplar as a function of pyrolysis temperature were studied by ultraviolet (UV) adsorption of dyes with positive, neutral, and negative charges to determine what factors had the greatest effect on adsorption of these dyes. It was found that conductivity of the biochars increased with pyrolysis temperature, and that this factor was more important than surface area in terms of adsorbing charged dyes. Both elm and poplar biochars were not effective in adsorbing neutral dyes. This research demonstrates that elm and poplar biochars adsorb charged (either positively or negatively) solutes more efficiently than uncharged ones because they carry both charges themselves. Therefore, these biochars would make excellent candidates as renewable filtration media for charged contaminants.